1990
DOI: 10.1063/1.459533
|View full text |Cite
|
Sign up to set email alerts
|

Shear stabilization of critical fluctuations in bulk polymer blends studied by small angle neutron scattering

Abstract: Smallangle neutron scattering by partially deuterated polymers and their blends J. Chem. Phys. 100, 3905 (1994); 10.1063/1.466325 Timeresolved smallangle neutron scattering study of spinodal decomposition in deuterated and protonated polybutadiene blends. I. Effect of initial thermal fluctuations J. Chem. Phys. 99, 4845 (1993); 10.1063/1.466225 Timeresolved smallangle neutron scattering study of later stage spinodal decomposition of a polymer blend AIP Conf. Proc. 256, 216 (1992); 10.1063/1.42443 Critical fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…The behavior of polymer blends under shear flow has recently been a subject of considerable interest from both the view point of theoretical research and industrial application because shear field is unavoidable in many polymer‐processing steps such as injection and extrusion moldings. Recent studies1–15 of polymer blends under shear field have shown the existence of shear‐induced mixing (SIM) and demixing (SID). Lyngaae‐Jorgensen and Sondergaard4, 5 found that in poly(methyl methacrylate) (PMMA)/poly(styrene‐co‐acrylonitrile) (SAN) at a critical shear rate, a light scattering pattern disappeared and SIM existed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of polymer blends under shear flow has recently been a subject of considerable interest from both the view point of theoretical research and industrial application because shear field is unavoidable in many polymer‐processing steps such as injection and extrusion moldings. Recent studies1–15 of polymer blends under shear field have shown the existence of shear‐induced mixing (SIM) and demixing (SID). Lyngaae‐Jorgensen and Sondergaard4, 5 found that in poly(methyl methacrylate) (PMMA)/poly(styrene‐co‐acrylonitrile) (SAN) at a critical shear rate, a light scattering pattern disappeared and SIM existed.…”
Section: Introductionmentioning
confidence: 99%
“…For polystyrene/polyvinyl methyl ether (PS/PVME), one of the extensively investigated polymer blends,3, 6–8, 11–15 it has been known that the phenomena of mixing, demixing, and two cloud points could occur under shear according to the applied shear rate and the experimental temperature. Mazich and Carr3 first reported that in a PS/PVME binary blend, shear flow increased the lower critical solution temperature (LCST) of the blend by 2–7 K. In their experiments, the abrupt change in the slope of the viscosity curve verse temperature was interpreted as an indication of the phase‐transition point.…”
Section: Introductionmentioning
confidence: 99%
“…In miscible blends, flow can affect the phase equilibrium; that is, it can change the phase diagram of the system 1. Although most of the studies indicate flow‐induced miscibility for such systems,2, 3 some researchers observed the opposite effect, flow‐induced demixing 4. Flow can also change the morphology of the polymer blends, causing breakup or coalescence of the dispersed‐phase droplets 5…”
Section: Introductionmentioning
confidence: 99%
“…A design by Keates et al7 was used to study structural changes in solutions of hydroxypropyl cellulose during flow with X‐ray scattering. A small‐angle neutron scattering instrument at the National Institute of Standards and Technology was used to study concentration fluctuations in polymer blends near their critical solubility temperature3 and to study shear‐induced order–disorder transitions in block copolymers 8. The size of the features that can be detected by neutron and X‐ray scattering is much smaller than that detectable by light scattering, which makes these techniques particularly attractive for certain applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The flow light-scattering method 18 has been used to investigate shear effects in a ternary system consisting of polystyrene͑PS͒, polybutadiene͑PB͒, and dio-ctylphthalate͑DOP͒ in previous reports. [8][9][10]13,19,20 DOP was chosen as an approximately neutral solvent to PS and PB.…”
Section: Introductionmentioning
confidence: 99%